Voicing the Technological Body: Some Musicological Reflections on Combinations of Voice and Technology in Popular Music Journal for Religion, Film and Media - Florian Heesch (Journal for Religion, Film and Media, 2016)
The article deals with interrelations of voice, body and technology in popular music from a musicological perspective. It is an attempt to outline a systematic approach to the history of music technology with regard to aesthetic aspects, taking the identity of the singing subject as a main point of departure for a hermeneutic reading of popular song. Although the argumentation is based largely on musicological research, it is also inspired by the notion of presentness as developed by theologian and media scholar Walter Ong. The variety of the relationships between voice, body, and technology with regard to musical representations of identity, in particular gender and race, is systematized alongside the following cagories: (1) the "absence of the body," that starts with the establishment of phonography; (2) "amplified presence," as a signifier for uses of the microphone to enhance low sounds in certain manners; and (3) "hybridity," including vocal identities that blend human body sounds and technological processing, whereby special focus is laid on uses of the vocoder and similar technologies.